That's a Great Answer!: Teaching Literature-Response Strategies to Elementary, Ell, and Struggling Readers - Boyles, Nancy N. (Maupin House, 2012)
Keywords: Reading comprehension; Study and teaching; United States; United States; Motivation in education; dept.rdg

Rethinking Small-Group Instruction in the Intermediate Grades: Differentiation That Makes a Difference - Boyles, Nancy N. (Maupin House Pub., 2010)
Keywords: Reading (Middle school); Guided reading; Group work in education; dept.rdg; faculty_collection

Learning character from characters - Boyles, N. (Educational Leadership, 2018)
Keywords: Challenged; Engaged; Language arts; Literacy: reading; School climate and culture; Social-emotional learning; Student behavior and discipline; dept.rdg; peer-reviewed; ⛔ No DOI found

Closing in on close reading - Boyles, Nancy (Educational Leadership, 2012)
tex.eissn: 1943-5878 tex.unique-id: ISI:000311877600006
Keywords: dept.rdg; peer-reviewed; ⛔ No DOI found

Close reading without tears - Boyles, Nancy (Educational Leadership, 2014)
tex.eissn: 1943-5878 tex.unique-id: ISI:000340866300005
Keywords: dept.rdg; peer-reviewed; ⛔ No DOI found

Pursuing the DEPTHS of knowledge - Boyles, Nancy (Educational Leadership, 2016)
tex.eissn: 1943-5878 tex.unique-id: ISI:000384400000009
Keywords: dept.rdg; peer-reviewed; ⛔ No DOI found

Common types of reading problems and how to help children who have them - Spear-Swerling, Louise (Reading Teacher, 2016)
Patterns of reading difficulty provide an educationally useful way to think about different kinds of reading problems, whether those problems are mainly experiential in nature (e.g., those common among English learners) or associated with disabilities (e.g., those typical of children with dyslexia). This article reviews research on three common patterns of poor reading: specific word-reading difficulties, specific reading-comprehension difficulties, and mixed reading difficulties. The purpose of the article is to explain how teachers can use assessments to identify individual struggling readers' patterns of reading difficulties, and how this information is valuable in differentiating classroom instruction and planning interventions.
13 citations (Crossref) [2023-10-31] tex.eissn: 1936-2714 tex.unique-id: ISI:000372317700007
Keywords: Diagnostic; Instructional intervention; Instructional strategies; dept.rdg; dept.sed; peer-reviewed; teaching strategies

How Portuguese and American teachers plan for literacy instruction. - Spear-Swerling, Louise; Lopes, Joao; Oliveira, Celia; Zibulsky, Jamie (Annals of Dyslexia, 2016)
This study explored American and Portuguese elementary teachers' preferences in planning for literacy instruction using the Language Arts Activity Grid (LAAG; Cunningham, Zibulsky, Stanovich, & Stanovich, 2009), on which teachers described their preferred instructional activities for a hypothetical 2-h language arts block. Portuguese teachers (N = 186) completed Portuguese versions of a background questionnaire and LAAG electronically, in Survey Monkey; American teachers (N = 102) completed identical English measures using paper and pencil. Results showed that teachers in both groups usually addressed comprehension and reading fluency on their LAAGs and that they also allocated the most time to these two areas. However, American teachers were more likely to include teacher-directed fluency activities, whereas Portuguese teachers were more likely to include fluency activities that were not teacher directed. Significantly more American than Portuguese teachers addressed phonics in their planning, whereas significantly more Portuguese than American teachers addressed writing processes such as revision. Both groups of educators demonstrated large variability in planning, with many teachers omitting important components of literacy identified by researchers, for writing as well as reading. The study highlights the importance of providing teachers with comprehensive, research-based core literacy curricula as well as professional development on key components of literacy. Study findings also suggest significant relationships between orthographic transparency and teachers' instructional planning.
5 citations (Crossref) [2023-10-31] Place: United States Spear-Swerling, Louise. Department of Special Education and Reading, Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, USA. SPEARSWERLL1@southernct.edu. Lopes, Joao. School of Psychology, Department of Applied Psychology, University of Minho, Campus de Gualtar, 4710-057, Braga, Portugal. Oliveira, Celia. Lusofona University of Porto, Rua Augusto Rosa, no 24, 4000-098, Porto, Portugal. Zibulsky, Jamie. Psychology Department, T-WH1-01, Fairleigh Dickinson University, 1000 River Road, Teaneck, NJ, 07666, USA.
Keywords: *Language Arts; *Literacy; *School Teachers; *Teacher Training; Adult; Comprehension; Cross-linguistic; Curriculum; Female; Humans; Language Arts; Literacy; Male; Phonetics; Portugal; Reading; School Teachers; Teacher Training; Teacher beliefs; Teacher education; Teacher knowledge; United States; Writing; Young Adult; adult; comprehension; curriculum; dept.rdg; dept.sed; female; human; language; literacy; male; phonetics; school teacher; teacher training; young adult

What's a middle school teacher to do? Five evidence-based practices to support English learners and students with learning disabilities - Hovey, Katrina A.; Miller, Rhonda D.; Kiru, Elisheba W.; Gerzel-Short, Lydia; Wei, Yan; Kelly, Jerae (Preventing School Failure: Alternative Education for Children and Youth, 2019)
General education teachers are challenged with meeting the unique instructional needs of every learner in their classrooms, which increasingly include English learners (ELs) and students with learning disabilities (LD). This article uses vignettes to demonstrate how a middle school content teacher uses five strategies: building prior knowledge, building vocabulary, explicit instruction, visual representation, and opportunities to respond to support his students. Each strategy is evidence based for ELs and for students who have an identified LD. Research supports that ELs and students with LD benefit from specific instructional strategies that enhance the accessibility of course content and potentially improve learning outcomes. © 2019, © 2019 Taylor & Francis Group, LLC.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-310-082-508-391, pop00124 tex.type: [object Object]
Keywords: English learners; dept.rdg; dept.sed; evidence-based strategies; instructional practices; learning disabilities; peer-reviewed

Engaging culturally and linguistically diverse families of children with disabilities - Gerzel-Short, Lydia; Kiru, Elisheba W.; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan; Miller, Rhonda D. (Intervention in School and Clinic, 2019)
Classrooms are increasingly more diverse, and student success can be enhanced through family engagement, especially for culturally and linguistically diverse (CLD) students with disabilities. Too often teachers are stymied by how to engage CLD families of children with disabilities. Common practices of parent involvement are ineffective and fail to appreciate families as members of the educational team. Family engagement seeks to establish and maintain authentic family-school partnerships based on mutual respect and shared agency for student academic and social success. This column provides specific family engagement strategies that teachers and schools can implement in an effort to provide reciprocal collaboration.
9 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000490317000008, lens.org/119-272-627-527-661 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: cultural and linguistic diversity; dept.rdg; dept.sed; disabilities; diverse families; family engagement; family-school collaboration; multicultural; peer-reviewed

Coteaching in content area classrooms: Lessons and guiding questions for administrators - Sinclair, Anne C.; Bray, Laura E.; Wei, Yan; Clancy, Erin E.; Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J. (NASSP Bulletin, 2018)
Secondary school administrators increasingly include students with disabilities in general education classrooms with coteaching models. Theoretically, coteaching enables two educators to attend to the learning needs of students with disabilities while exposing them to grade-level content area instruction. However, our study on teachers’ perceptions of coteaching found that teachers often viewed their schools’ leadership decisions as adversely affecting their ability coteach effectively. The purpose of this article is to provide administrators with an overview of common coteaching models, summarize findings from our study on teachers’ perceptions of how their schools’ leadership influenced their coteaching practices, and provide a set of guiding questions to consider when seeking to support coteaching. © 2018 SAGE Publications.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-514-925-194-03X, pop00123 tex.type: [object Object]
Keywords: coteaching; dept.rdg; dept.sed; inclusion; instructional leadership; peer-reviewed; professional development

A high school replication of targeted professional development for classroom management - Freeman, Jennifer; Kowitt, Jennifer; Simonsen, Brandi; Wei, Yan; Dooley, Kate; Gordon, Lola; Maddock, Eleanor (Remedial and Special Education, 2018)
In areas of emerging research, such as supporting teachers' classroom management, replication of research is critical to ensuring that recommendations for the field are based on sound science and appropriate for the contexts to which they are being applied. This article describes a replication of research on efficient professional development supports for teachers' classroom managements in a new context: high school classrooms. Data did not support a functional relation between teachers' use of specific praise and the targeted professional development and self-management in the high school setting. Results of this study highlight the critical importance of replication in education research. Based on our findings and our experience conducting this study, we suggest several possible adaptations may be necessary for successful replication at the high school level.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-228-318-057-658, pop00145 tex.type: [object Object]
Keywords: behavior; dept.rdg; dept.sed; inservice training; management; peer-reviewed; personnel preparation; research methodology; secondary; single-subject; staff development/inservice

Reading comprehension and co-teaching practices in middle school English language arts classrooms - Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J.; Mitchell, Marisa; Clancy, Erin; Davidson, Kimberly A.; Sinclair, Anne C.; Wei, Yan (Exceptional Children, 2018)
This study reports practices implemented in over 2,000 minutes by 16 middle school special education and general education co-teaching pairs in English language arts classes. We report the extent to which teachers integrated literacy activities that support reading comprehension, the co-teaching models used, and the frequency with which each teacher led instruction. We also report the types of grouping structures teachers used and the extent to which teachers interacted with students with disabilities. Finally, we report the types of text used. Observations revealed that more than half of time spent on literacy activities involved reading aloud or silently with no co-occurring literacy instruction that supports reading comprehension. Students with disabilities spent a majority of their time in whole-class instruction or working independently with little teacher interaction. Special education teachers spent most of their time supporting whole-class instruction led by the content-area teacher. Implications and directions for future research are provided.
37 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-264-196-907-683, pop00086 tex.type: [object Object]
Keywords: dept.rdg; dept.sed; peer-reviewed

Higher education and disability: A systematic review of assessment instruments designed for students, faculty, and staff - Lombardi, Allison; Gelbar, Nicholas; Dukes, III, Lyman L.; Kowitt, Jennifer; Wei, Yan; Madaus, Joseph; Lalor, Adam R.; Faggella-Luby, Michael (Journal of Diversity in Higher Education, 2018)
In this study, the literature in disability and higher education was examined, with a specific focus on assessment instruments. Published articles (n = 203) on development of new or refinement of existing instruments were reviewed for traits measured and psychometric rigor reported. Findings showed instruments are intended for professionals and students, and of the student instruments, broad categories are academic, nonacademic, and specific to a disability diagnosis. Not all instruments are limited to students with disabilities; many of the reviewed instruments can be utilized in higher-education settings on all students, faculty, and staff, regardless of disability. The implications of the findings undergird the urgency to prioritize disability as a facet of diversity within higher-education scholarship, and furthermore aid this prioritization by providing a catalogue of robust instruments to researchers and practitioners.
25 citations (Crossref) [2023-10-31] tex.eissn: 1938-8934 tex.unique-id: ISI:000426973700003
Keywords: Disability; assessment; campus climate; dept.rdg; dept.sed; peer-reviewed; program evaluation

Leveraging information technology literacy to enhance college and career readiness for secondary students with disabilities - Lombardi, Allison; Izzo, Margo V.; Gelbar, Nicholas; Murray, Alexa; Buck, Andrew; Johnson, Victor; Hsiao, Jay; Wei, Yan; Kowitt, Jennifer (Journal of Vocational Rehabilitation, 2017)
BACKGROUND: In the 21st century, information technology (IT) literacy is crucial for all students, and may better prepare students with disabilities for transition to postsecondary employment or education. OBJECTIVE: In this study, the potential of IT literacy embedded into an online transition curriculum is explored in the context of secondary special education. The curriculum aligns with Common Core State Standards in English Language Arts that are relevant to reading comprehension, writing, as well as searching for and analyzing sources of information online. METHODS: A quasi-experimental pretest-posttest design was utilized in six high schools. RESULTS: Findings show that intervention group students improved in IT literacy; whereas, comparison group students did not make similar gains. CONCLUSION: Implications for embedding transition services into specific courses and curricula for secondary students with Individualized Education Programs (IEPs) are discussed. © 2017-IOS Press and the authors. All rights reserved.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-237-439-502-729, pop00111 tex.type: [object Object]
Keywords: Article; Transition; adolescent; attention deficit disorder; autism; career; career readiness; college; comprehension; controlled study; curriculum; dept.rdg; dept.sed; disability; education program; emotional disorder; employment; female; high school student; human; information technology; intellectual impairment; language disability; learning disorder; literacy; major clinical study; male; quasi experimental study; special education; technology; vocational education; writing